Reviewing COVID-19 Modelling amidst Recent United States Protests - Luther-King O. Fasehun (Ubiquity Press, 2020)
The unfortunate death of George Floyd in Minnesota, following police brutality, is deeply regrettable, and the ensuing protests in cities across the United States bring up issues on the potential impacts of the protests on the epidemiology of COVID-19 in the United States. Modelling scientists will need the best time-series estimates of the numbers of protesters in every city where protests took place; the length of time the protests were active, and what distance and routes were covered by the protesters; and the numbers and distribution of security personnel deployed to keep the protests safe, as well as curtail the chaotic exacerbations that were reported across many areas.